PENGARUH DISIPLIN KERJA TERHADAP KINERJA PEGAWAI PADA PT. PLN (PERSERO) DISTRIBUSI MAKASSAR - Salim, Agus; Mappatompo, Andi (UNIVERSITAS MUHAMMADIYAH MAKASSAR, 2019)
AbstractThis study aims to test the influence of work discipline on employee performance in PT. PLN (Persero) Makassar Distribution Regulatory Area.This research data was collected from 68 respondents working at PT. PLN (Persero) Makassar Distribution Regulatory Area.The statement was given using a questionnaire. Respondents' responses to the statements were then analyzed quantitatively. Quantitative analysis includes tests of validity, reliability, and simple linear regression analysis.The results of this study showed that work discipline variables have a dominant effect on employee performance at PT. PLN (Persero) Makassar Distribution Area. Partially the variables of work discipline have a significant effect on the performance of employees with a thitung of 8,499and a significant value of 0.000 has a significant effect on the performance of employees, the most dominant affects the performance of employees at PT. PLN (Persero) Makassar Distribution Regulatory Area is a work discipline variable with a regression coefficient of 0.851Keywords: Work Discipline, Employee Performance